Film Is not dead : a digital photographer's guide to shooting film - Canlas, Jonathan; Kalp, Kristen (Berkeley, CA : New Riders, 2012)
Presents a beginner's guide to film photography, discussing the best cameras, lenses, films, and processing for the medium, and describes why film photography still provides a unique look unattainable by digital means.
Keywords: Photography; Photography -- Films